(untitled) (Fiep Bulletin - online, 2011)
The network of health care services to elderly health care organized by Unified Health System (SUS) are not still suited to the requirements and specificities of health in this age group and are therefore seen a breach of the principle of completeness, in the public emergency services. This descriptive and exploratory study aims to characterize the elderly treated in emergency rooms of two hospitals in a Brazilian city of medium size. The data collection was done using semi-structured interview accompanied of form with open and closed questions related to current health status and socio- demographic factors, besides the information in hospital records. The results indicate that among the respondents, 60.0% are illiterate, 55.0% were married, 31.0% widowed, 47.0% had 6 to 10 children, 57.0% retired, 81.2 % with income between 1 to 3 minimum wages, 44.2% live with children and 98.0% have no health insurance. On morbidity, 53.4% have cardiovascular diseases, 68.5% were hospitalized, and, of these 53.0% were treated without going through the screening service at both institutions. These results allow us to conclude that the current demographic and health profiles require to establish new strategies to cope the increase of potentially dependent elderly with low socioeconomic status,with chronic diseases and consuming of disproportionate share of resources health.